2019
DOI: 10.21608/jappmu.2019.43006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Different Levels from Heat Protected Soybean Meal Protein in Diets of Growing Rahmani Lambs on Digestibility Coefficients, Feeding Values and Growth Performance

Abstract: Fifteen weaning Rahmani lambs with an average live body weight 19±0.5 kg and 4 months age were randomly assigned into three groups (each of 5 lambs) to study the effect of heat protected soybean meal protein diets at 145°C in a forced air oven for 4 hrs on nutrients digestibility as well as feeding values and their reflection on growth performance of growing lambs. Animals were fed for 120 days feeding period on the same three experimental diets. Control fed diet containing soybean meal (15%) without treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…[18] revealed that despite the animals consuming high-quality feed, the limits of muscular development could not be overcome. [10] That providing soy groats in insufficient amounts can result in protein being absorbed into the small intestine.…”
Section: Meat Percentagementioning
confidence: 99%
“…[18] revealed that despite the animals consuming high-quality feed, the limits of muscular development could not be overcome. [10] That providing soy groats in insufficient amounts can result in protein being absorbed into the small intestine.…”
Section: Meat Percentagementioning
confidence: 99%